High cardiovascular event rates occur within the first weeks of starting hemodialysis - Eckardt, Kai-Uwe; Gillespie, Iain A.; Kronenberg, Florian; Richards, Sharon; Stenvinkel, Peter; Anker, Stefan D.; Wheeler, David C.; De Francisco, Angel L.; Marcelli, Daniele; Froissart, Marc; Floege, Juergen (Kidney International, 2015)
Early mortality is high in hemodialysis (HD) patients, but little is known about early cardiovascular event (CVE) rates after HD initiation. To study this we analyzed data in the AROii cohort of incident HD patients from over 300 European Fresenius Medical Care dialysis centers. Weekly rates of a composite of CVEs during the first year and monthly rates of the composite and its constituents (coronary artery, cerebrovascular, peripheral arterial, congestive heart failure, and sudden cardiac death) during the first 2 years after HD initiation were assessed. Of 6308 patients that started dialysis within 7 days, 1449 patients experienced 2405 CVEs over the next 2 years. The first-year CVE rate (30.2/100 person-years; 95% CI, 28.7-31.7) greatly exceeded the second-year rate (19.4/100; 95% CI, 18.1-20.8). Composite CVEs were highest during the first week with increased risk compared with the second year, persisting until the fifth month. Except for sudden cardiac death, temporal patterns of rates for all CVE categories were very similar, with highest rates during the first month and a high-risk period extending to 4 months. Higher or lower cumulative weekly dialysis dose, lower blood flow, and lower net ultrafiltration during dialysis were associated with CVE during the high-risk period, but not during the post high-risk period. Thus, the incidence of CVE in the first weeks after HD initiation is much higher than during subsequent periods which raises concerns that HD initiation may trigger CVEs.
EVALuna2:3778